1999
DOI: 10.1007/s002239900572
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Velocity of Trabecular Cubes Reflects Mainly Bone Density and Elasticity

Abstract: Studies have indicated that quantitative ultrasound (QUS) variables may be influenced by the mechanical properties of bone which in turn are determined by bone's material and structural properties. However, from these studies it is unclear what role density, elasticity, and structure play in determining velocity. Eighteen defatted, 12-mm cubic trabecular bone specimens were cut from cadaveric specimens. Amplitude-dependent speed of sound (SOS) using a single point QUS system was assessed in three orthogonal ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
0
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(102 citation statements)
references
References 36 publications
11
85
0
6
Order By: Relevance
“…15,32,33,35 In the present study, SOS accounted for 84%-92% of the variance in FEA-estimated Young's modulus in each of the three perpendicular directions, and for 89% when the directions were pooled. In previous studies, the associations between stiffness and ultrasound velocity in human bone specimens were reported as r values between 0.44 and 0.77, 12,15,36 and r 2 values between 0.41 and 0.72. 5,17 In the bovine model, r 2 values of between 0.79 and 0.83 have been reported.…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…15,32,33,35 In the present study, SOS accounted for 84%-92% of the variance in FEA-estimated Young's modulus in each of the three perpendicular directions, and for 89% when the directions were pooled. In previous studies, the associations between stiffness and ultrasound velocity in human bone specimens were reported as r values between 0.44 and 0.77, 12,15,36 and r 2 values between 0.41 and 0.72. 5,17 In the bovine model, r 2 values of between 0.79 and 0.83 have been reported.…”
Section: Discussionmentioning
confidence: 45%
“…These studies differed also with respect to location and type of trabecular bone used (human calcaneal, lumbar spine or femoral neck bone samples, 5,12,15,36 bovine femoral bone samples, 35 or both human and bovine samples, 17 ), the preparation and size of the bone samples, and the ultrasound system used, so it is difficult to compare the results with our study. Nevertheless, it seems evident that the associations between SOS and stiffness, estimated by FEA in the present study, are stronger than the associations reported in the studies in which stiffness was assessed by mechanical testing.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations